2020
DOI: 10.1038/s41929-020-0455-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-aqueous gas diffusion electrodes for rapid ammonia synthesis from nitrogen and water-splitting-derived hydrogen

Abstract: The procedures and materials for nitrogen reduction outlined below have been optimized for reliable ammonia production. However, certain deviations from the procedure and material vendors, which are specifically called out in-text and in prior work, 1 may lead to poorer ammonia production. We recommend closely following the procedure for reproducibility and high yields. MaterialsTetrahydrofuran (THF, 99+%, stabilized with BHT) and molecular sieves (3Å, 4-8 mesh) were purchased from Acros Organics. Lithium tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
353
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(400 citation statements)
references
References 50 publications
(11 reference statements)
10
353
0
Order By: Relevance
“…Such a trap approach described above is not directly applicable to studies with non-aqueous electrolytes, which arguably provide the only known conditions that enable genuine NRR under low temperature and pressure 9 . The use of solid-state NO x purifying columns 9 is more convenient in this case, although if such columns are not available, several high-volume traps filled with an organic solvent of interest installed between the aqueous NO x scrubber and the electrochemical cell might be used as well 39 .…”
Section: Andmentioning
confidence: 99%
“…Such a trap approach described above is not directly applicable to studies with non-aqueous electrolytes, which arguably provide the only known conditions that enable genuine NRR under low temperature and pressure 9 . The use of solid-state NO x purifying columns 9 is more convenient in this case, although if such columns are not available, several high-volume traps filled with an organic solvent of interest installed between the aqueous NO x scrubber and the electrochemical cell might be used as well 39 .…”
Section: Andmentioning
confidence: 99%
“…A similar strategy has already been used successfully to increase the selectivity of electrochemical N 2 reduction (where the parasitic reaction is hydrogen evolution). [41][42][43][44] Limited access to holes can for instance be achieved by limiting conductivity to the surface. For TiO 2 this could be achieved by controlling the thickness of a non-conducting TiO 2 lm on the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…RCWW had high levels of NH 3 throughout the year, as seen in Figure 3. Lazouski et al demonstrated that the use of conventional gas diffusion electrodes can be used to produce NH 3 fertiliser from nitrogen and water-splitting-derived hydrogen, which could potentially be derived from wastewater [42]. However, this method is only capable of producing a NH 3 fertiliser, whereas the use of membrane distillation allows for the production of (NH 4 ) 2 SO 4 .…”
Section: Identification Of Viable By-products From Rendering Condensatementioning
confidence: 99%